TEleRehabilitation Nepal (TERN) for People With Spinal Cord Injury and Acquired Brain Injury: A Feasibility Study. (October 2022) - Dhakal, Raju; Baniya, Mandira; Solomon, Rosie M; Rana, Chanda; Ghimire, Prajwal; Hariharan, Ram; Makower, Sophie G; Meng, Wei; Halpin, Stephen; Xie, Sheng Quan; O'Connor, Rory J; Allsop, Matthew J; et al.
BACKGROUND: Spinal Cord Injury (SCI) or Acquired Brain Injury (ABI) leads to disability, unemployment, loss of income, decreased quality of life and increased mortality. The impact is worse in Low-and Middle-Income Countries (LMICs) due to a lack of efficient long-term rehabilitative care. This study aims to explore the feasibility and acceptability of a telerehabilitation programme in Nepal. METHODS: Prospective cohort feasibility study in a community setting following discharge from a specialist rehabilitation centre in Nepal. Patients with SCI or ABI who had previously accessed specialist rehabilitation were connected to a specialist Multidisciplinary Team (MDT) in the centre through a video conference system for comprehensive remote assessments and virtual individualised interventions. Data were captured on recruitment, non-participation rates, retention, acceptability (via end-of-study in-depth interviews with a subset of participants) and outcome measures including the Modified Barthel Index (MBI), Depression Anxiety Stress Scale (DASS) and EuroQol-5D (EQ-5D), completed pre- and post-programme. RESULTS: 97 participants with SCI (n = 82) or ABI (n = 15) discharged from the centre during an 18-month period were approached and enrolled on the study. The telerehabilitation programme facilitated the delivery of support around multiple aspects of rehabilitation care, such as spasticity treatments and pain management. Outcome measures indicated a significant improvement in functional independence ( P  < .001), depression, anxiety and stress ( P  < .001) and quality of life ( P  < .001). Qualitative interviews (n = 18) revealed participants found the programme acceptable, valuing regular contact and input from MDT professionals and avoiding expensive and lengthy travel. CONCLUSION: This is the first study in Nepal to identify telerehabilitation as a feasible and acceptable approach to augment the provision of specialist rehabilitation. Future research is needed to assess the suitability of the programme for other conditions requiring specialist rehabilitation and determine the mechanisms underpinning improved outcomes for people with SCI or ABI. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT04914650